Analisis Faktor - Faktor Yang Berpengaruh Terhadap Keputusan Pembelian Konsumen E-Commerce Tokopedia Pada Mahasiswa Fakultas Sains Dan Teknologi Universitas Prima Indonesia - Shannen Fania Halim; Winda Sri Astuti Doloksaribu; Chyntia Lienedy; Acai Sudirman (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the effect of promotion on e-commerce Tokopedia purchase decision, determine the effect of service quality on e-commerce Tokopedia purchase decision, determine the effect of customer review on e-commerce Tokopedia purchase decision, and determine the effect of promotion, service quality, and customer review on e-commerce Tokopedia purchase decision. This type of research uses descriptive quantitative methods. The population in this study amounted 788 people with a sample of 89 respondents. The data analysis used in this study is Instrument Test, Classical Assumption Test, Multiple Linear Regresion Analysis, Hypotesis Test, and Coefficient of Determination Test (R2). The results of this study are promotion has a positive and significant effect on purchase decision, service quality has a positive and significant effect on purchase decision, customer review has a positive and significant effect on purchase decision, and promotion, service quality and customer review has a positive and significant effect on purchase decision on e-commerce Tokopedia in students of Science and Technology Faculty Prima Indonesia University. Keywords: Promotion, Service Quality, Customer Review, Purchase Decision